FORCED HAPPINESS AS A MODERN SOCIO AND CULTURAL IMPERATIVE - H. V. Khodus (Antropologìčnì Vimìri Fìlosofsʹkih Doslìdžen')
Purpose. In this article is an attempt to "read" cultural code of the phenomenon of happiness in actual social circumstances. The research was primarily focused on the specifics of the contemporary cultural situation, which determines the emotional infrastructure of individuals’ life. Methodology. The number of concepts that were proposed by M. Foucault, N. Elias, in particular – «configurationally balance of power», «culture of yourself», «take care of yourself», «practice of yourself», "the discourse of power/knowledge" are proposed as a heuristic resource that allows to comprehend the transit of value-semantic codes of the happiness phenomenon. Such analytical optics enable reading of contemporary social reality as a discursive space that permeated with visual aestheticization of various emotions, legitimized with knowledge/power. This disciplinary discourse not only codifies the "correct" expression of emotions, but also culturally encodes the hierarchy of these "correct" emotions. Scientific novelty. It is proved that a characteristic feature of current modernity (available in Ukrainian realities) is the change in happiness status, its transformation into "normative" emotion that individuals should feel and show. In other words, the cult of happiness becomes dominant cultural imperative, a duty, acting as a moral duty. It is argued that "the forced happiness" is a social effect of the therapeutic culture, which streamlines the emotional life of the individual, interpersonal relationships, scenarios of success and happiness. The key role of cultural mediators, commercial narratives (Internet, media) in the design and promotion of the ideology of "forced happiness" is justified. Conclusions. The proposed research approach allows deconstructing the emotional regime of modernity in the aspect of problematization the phenomenon of happiness. The idea is that the right to happiness, to private pleasure and self-care are the basic ideas of the Enlightenment and transformed into a cult object of enormous industry in the modern consumer society, the viability of which depends on the effectiveness of the symbolic goods consumption. Thus, the defining feature of the modern market society becomes the intensification practices of fun, the emancipation of desires that not only frees the individual, does not make him happy, and on the contrary, the individual exists in the atmosphere of constant existential anxiety, which is expressed in the sense of danger not to be happy, not fit within the "emotional regime".